Doubling Farmers Inccome through fertigation in Bt II cotton in Maharashtra - Naib, S D (Indian Farming, 2017)
In the village Govari of district Chandrapur, cotton is the major grown crop. After over coming the constraints in cottonyield and guiding the farmers for following the best management practices, change in the yield of cotton crop was seen on a big scale.